Análisis de la cultura tributara de los comerciantes del puerto Masusa, Iquitos – 2022 - Avila Coronado, Ingrid Talia (2023)
The present study titled “Analysis of the Tax Culture of the Merchants of Puerto Masusa, Iquitos - 2022” was carried out with the objective of determining the level of Tax Culture of the merchants of this port, to achieve this, a descriptive investigation was carried out. non-experimental design, where 11 merchants who voluntarily decided to participate in this research work were taken as the study population, to whom the survey technique was applied and the questionnaire was used as an instrument; According to the analysis of the results, it was determined that the merchants of Puerto Masusa do not have training in tax issues, it is concluded that the workers have a medium level of Tax Culture.